Anticancer effects of olive oil polyphenols and their combinations with anticancer drugs - Torić Jelena; Marković Ana Karković; Brala Cvijeta Jakobušić; Barbarić Monika (Acta Pharmaceutica)
Cancer presents one of the leading causes of death in the world. Current treatment includes the administration of one or more anticancer drugs, commonly known as chemotherapy. The biggest issue concerning the chemotherapeutics is their toxicity on normal cells and persisting side effects. One approach to the issue is chemoprevention and the other one is the discovery of more effective drugs or drug combinations, including combinations with polyphenols. Olive oil polyphenols (OOPs), especially hydroxytyrosol (HTyr), tyrosol (Tyr) and their derivatives oleuropein (Ole), oleacein and oleocanthal (Oc) express anticancer activity on different cancer models. Recent studies report that phenolic extract of virgin olive oil may be more effective than the individual phenolic compounds. Also, there is a growing body of evidence about the combined treatment of OOPs with various anticancer drugs, such as cisplatin, tamoxifen, doxorubicin and others. These novel approaches may present an advanced strategy in the prevention and treatment of cancer.